Short Communication: Effectiveness of nuclear gene in species and subspecies determination of captive orangutans - MUHAMMAD NURISMADEE ABDUL-MANAN; MOHD-RIDWAN ABD RAHMAN; NOR AIFAT RAHMAN; NUR AZIMAH OSMAN; MUHAMMAD ABDUL-LATIFF ABU BAKAR; SABAPATHY DHARMALINGAM; BADRUL MUNIR MD ZAIN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Abdul-Manan MN, Mohd-Ridwan AR, Aifat NR, Osman NA, Abdul-Latiff MA, Dharmalingam S, Md-Zain BM. 2020. Short Communication: Effectiveness of nuclear gene in species and subspecies determination of captive orangutans. Biodiversitas 21: 3665-3669. Genetic identification of captive orangutans is of paramount importance in providing a correct identity that is essential for captive management. Thus, the utility of nuclear DNA sequences was tested in this study to identify the genetic identity of captive orangutans at Bukit Merah Orang Utan Island. Out of 24 DNA samples that were successfully extracted, only 10 orangutan samples were successfully sequenced for the von Willebrand factor (vWF) gene. From the results, this gene was able to separate the genus Pongo at the species level. Distance and character analyses indicated that a clear separation between P. pygmaeus and P. abelii at the species level. However, the degree of separation at species level was indicated in tree topology with moderate bootstrap values. At the subspecies level of P. pygmaeus, this gene was unable to show a clear separation between three Bornean subspecies. All the subspecies were formed clade together with each other. The vMF gene is a good nuclear gene for the study of phylogenetic relationships of orangutans in captivity at the species level, but the genetic identification at subspecies level in the genus level remains unclear. We suggest that future studies should involve multiple independent nuclear markers to increase the probability of getting reliable results.